Democratic Literacy of First-time Voters in the 2024 Election Through Social Media Consumption - Olivia Lewi Pramesti; Birgitta Bestari Puspita; Nobertus Ribut Santoso; Theresia Diyah Wulandari (Profetik: Jurnal Komunikasi, 2025)
Social media plays a significant role in giving information to first-time voters. It can also be a public sphere for first-time voters to participate in the Presidential Election. The knowledge of first-time voters is influenced by sociological and psychological factors, which are different from the previous generation. This study aims to know democracy literacy among first-time voters, particularly in using social media. Democratic literacy encourages citizens to speak up bravely and criticize the policy. This study uses qualitative research with the Focus Group Discussion method with eight participants. The participants of the FGD are first-time voters actively involved in the student press. The results show that first-time voters have a foundation of democratic literacy so that they are able to analyse the political issues on social media and the hoaxes around political issues. Social media becomes the primary medium for the participants to access political issues, ranging from Instagram, X, and TikTok. These first-time voters conduct only two activities when using social media, namely consuming and participating in political issues, such as giving likes on a post from politicians. However, they do not create political information on social media and choose private spaces to discuss political issues because they are aware of the risks and consequences in discussing politics in social media.